Leading the Malcolm Baldrige Way : How World-Class Leaders Align Their Organizations to Deliver Exceptional Results - Kendall, Kay; Bodinson, Glenn (McGraw-Hill's AccessEngineering., 2017)
The definitive guide to implementing Baldrige Criteria in any organization-from the team that coached multiple Malcolm Baldrige Award winners.